Evaluating the Association Between Hearing Loss and Falls in Adults With Vestibular Dysfunction or Nonvestibular Dizziness. Issue 3 (1st November 2021) - Huang, Ryan J.; Pieper, Carl F.; Whitson, Heather E.; Garrison, Douglas B.; Pavon, Juliessa M.; Riska, Kristal M.
Abstract : Objectives: Although emerging evidence suggests that hearing loss (HL) is an independent risk factor for falls, it is unclear how HL may impact falls risk in adults with vestibular dysfunction and nonvestibular dizziness. The purpose of this study was to characterize the impact of HL on falls in patients with vestibular dysfunction and nonvestibular dizziness relative to a group of patients without dizziness. In addition, this study aimed to evaluate whether there was an interactive effect between HL and vestibular dysfunction or nonvestibular dizziness on the odds of falling. Design: The authors conducted a retrospective cross-sectional study of 2, 750 adult patients with dizziness evaluated at a tertiary care center vestibular clinic between June 1, 2015, and October 7, 2020. Only patients with available self-reported falls status, as extracted from the electronic medical record, were included. Patients were classified into the following diagnostic groups based on rotary chair testing and videonystagmography: benign paroxysmal positional vertigo (BPPV, n = 255), unilateral vestibular hypofunction (UVH, n = 456), bilateral vestibular hypofunction (BVH, n = 38), central dysfunction (n = 208), multiple diagnoses (n = 109), and dizzy, nonvestibular (n = 1, 389). A control group of patients without dizziness (n = 295) was identified by a random sample of audiology patients. Degree of HL was characterized by the 4-frequency pure tone average (PTA) (0.5, 1, 2, and 4 kHz) of the better hearing ear. Demographic variables, comorbidities, cognitive impairment status, and falls-associated medications were extracted from the electronic medical record and included as covariates during analysis. Potential associations between PTA and falls status and possible interactions between diagnostic group and PTA were explored using multivariate logistic regression. Results: The BVH and central dysfunction groups had the highest rates of self-reported falls at 26.3% and 26.9%, respectively. The control group had the lowest rate of self-reported falls at 6.4%. With the exception of the multiple diagnoses group, all diagnostic groups had elevated odds of falling compared with the control group, when adjusting for demographics, comorbidities, cognitive impairment status, and falls-associated medications. There was no significant association between degree of HL and falls status (odds ratio [OR] = 1.02; 95% confidence interval [CI] = 0.93, 1.11; p = 0.713) when adjusting for diagnostic group and all other covariates. Furthermore, there were no significant interactions between diagnostic group and degree of HL on the odds of falling. Conclusions: These results indicate that HL was not associated with falls in patients with vestibular dysfunction or nonvestibular dizziness, while adjusting for demographics, comorbidities, and falls-associated medications. There was no significant interactive effect observed between HL and vestibular dysfunction or nonvestibular dizziness on the odds of falling. As previously reported, vestibular dysfunction and nonvestibular dizziness were independently associated with falls relative to a group of patients without dizziness. A population-based study utilizing more robust falls data is needed to explore a potential association between HL and falls in those with vestibular dysfunction.